RANCANG RANCANG BANGUN SISTEM PEMBELIAN VOUCHER GAME ONLINE BERBASIS WEBSITE MENGGUNAKAN TEKNOLOGI MERN STACK DENGAN MODEL WATERFALL (Studi Kasus : Good Gaming Store) - Fajar Setiawan; Hadi Zakaria (CV. Multi Kreasi Media, 2022)
Games are software that is made to fill free time to play games as entertainment. Each game player can purchase items used to win the game, and items can enhance the abilities of the actor in the game itself. In purchasing game vouchers players want an easy, fast and cheap payment system. Based on the above problems, it is necessary to create a web-based application that can help players buy vouchers in the game. What is done in this system displays game details that suit your needs and can make direct purchases safely, easily and quickly. In the creation of this system uses MERN technology and Visual Studio Code as writing lines of code. The purpose of creating this web-based online game voucher purchase system is to make it easier for users to make game voucher purchases and provide detailed information about the online game voucher, as well as assist the store owner in filling out the game voucher.